2012
DOI: 10.1038/eye.2011.362
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orbital decompression surgery on refraction and intraocular pressure in patients with thyroid orbitopathy

Abstract: Purpose To investigate the effect of orbital decompression surgery in thyroid orbitopathy (TO) on both refractive status and intraocular pressure (IOP). Patients and methods A prospective, multicentre, consecutive audit of patients undergoing thyroid decompression surgery. Indications for surgery included cosmetically unacceptable proptosis or corneal exposure. Exclusion criteria included the following: previous orbital surgery, glaucoma, corneal disease, steroid use in the preceding 12 months, or an acute opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…In thyroid eye disease, both decompression [ (Norris et al 2012) and references therein] and recession of the inferior rectus muscle (Gomi et al 2007) may contribute to reduction in IOP. The most likely mechanism is a reduction in retrobulbar and episcleral venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid eye disease, both decompression [ (Norris et al 2012) and references therein] and recession of the inferior rectus muscle (Gomi et al 2007) may contribute to reduction in IOP. The most likely mechanism is a reduction in retrobulbar and episcleral venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,14,16 Various levels of IOP reduction after orbital decompression were reported probably as a result of different surgical techniques and patient selection criteria. Danesh-Meyer et al 14 found a mean IOP decrease of 4.1 mmHg in 116 eyes, whereas Norris et al 20 reported 2.28 mmHg IOP reduction after orbital decompression performed on 52 orbits of 33 GO patients. In addition to previous studies we also demonstrated that the decrease in IOP was realised together with the increase in SOV-BFV and comparable in most GO cases regardless the presence of DON.…”
Section: Discussionmentioning
confidence: 93%
“…[8][9][10] However, whether or not myopic shift is induced by surgery is uncertain. In our study, the mean spherical refraction was decreased by 0.38 D with the myopic change.…”
Section: Resultsmentioning
confidence: 99%
“…For patients undergoing successful decompression, we can estimate ophthalmic status prior to the start of proptosis. Although there have been studies reporting the effect of orbital decompression on refraction, [8][9][10] whether or not refractive error is induced or not remains uncertain. In this study, we assessed the biometrics of the eyeball, including axial length (AL), anterior chamber depth (ACD), lens thickness (LT), refraction, keratometry, and aberration, before and after orbital decompression in order to estimate the correlation between proptosis progression and biometric changes.…”
Section: Introductionmentioning
confidence: 99%